OP04 Turning sweet in inflammatory bowel disease: glycans as novel immunomodulators of T-cell-mediated immune response. (25th January 2019) - Dias, A; Pereira, M; Correia, A; Alves, I; Pinto, V; Azevedo, L; Maia, L; Marcos-Pinto, R; Vilanova, M; Lago, P; Pinho, S
Abstract: Background: Mucosal T lymphocytes from patients with ulcerative colitis (UC) were previously shown to display a deficiency in branched N-glycans that was associated with disease severity. 1, 2 However, whether this altered glycosylation pathway shapes the course of the T-cell response constituting a targeted-specific mechanism in UC remains largely unknown. Moreover, the predictive capacity of this colonic glycosignature in terms of disease course and therapy response was investigated. Methods: We used a multi-disciplinary approach that gathers in vitro, ex vivo, mouse models of disease and clinical validation in human samples. Human ex vivo CD3+ T cells (from intestinal lamina propria) were purified from fresh colonic biopsies and blood of 75 UC patients with active disease and with different Mayo endoscopic subscores. T cells were cultured and supplemented with increasing doses of the simple glycan N -acetylglucosamine (GlcNAc). The impact on T-cell-mediated immune response was analysed by assessing: T-cell proliferation; T-cell activation and differentiation; cytokine profile; TCR signalling and the glycophenotype of T-cells were also determined. Additionally, colitis were induced (with DSS) in null/heterozygous mouse models displaying a deficiency in the branched N-glycosylation pathway (MGAT5−/−; MGAT5+/−); treatment with GlcNAc orally and/or with enemas was performed and the immunomodulatory effects of GlcNAc were evaluated. Results: We demonstrated that metabolic supplementation of ex vivo mucosal T cells from active UC patients with GlcNAc resulted in enhancement of branched N-glycosylation in the T-cell receptor (TCR), leading to suppression of T-cell growth, inhibition of the Th1/Th17 immune response, and controlled T-cell activity. We further demonstrated that mouse models displaying a deficiency in the branched N-glycosylation pathway (MGAT5−/−, MGAT5+/−) exhibited increased susceptibility to severe forms of colitis and early-onset disease. The treatment of these mice with GlcNAc significantly reduced disease severity and suppressed disease progression due to a controlled T-cell-mediated immune response at the intestinal mucosa. 3 Furthermore, we also showed that the levels of expression of branched N-glycans analysed in colonic biopsies of UC patients close to diagnosis predicts the failure to standard therapy. 4 Conclusions: We propose glycans as novel immunomodulators in IBD, further disclosing a promising predictive glycobiomarker associated with therapy response. Note: This work was sponsored by ECCO grant 2017. References 1. Pinho SS, Reis CA. Glycosylation in cancer: mechanisms and clinical implications. Nat Rev Cancer 2015;15:540–55. 2. Dias AM, Dourado J, Lago P, et al. Dysregulation of T cell receptor N-glycosylation: a molecular mechanism involved in ulcerative colitis. Hum Mol Genet 2014;23:2416–27. 3. Dias AM, Correia A, Pereira MS, et al . Metabolic control of T cell immune response through glycans in inflammatory bowel disease. Proc Natl Acad Sci USA 2018;115:E4651–60. 4. Pereira MS, Maia L, Azevedo LF, et al. A (glyco)biomarker that predicts failure to standard therapy in ulcerative colitis patients. J Crohns Colitis 2018. doi:10.1093/ecco-jcc/jjy139.